Parent training and joint engagement in young children with autism spectrum disorder. (March 2017) - Killmeyer, Susan; Kaczmarek, Louise
Children are diagnosed at increasingly earlier ages with autism spectrum disorder, characterized by diminished levels of social orienting and engagement. Parent-mediated interventions incorporating the use of responsive parent behaviors have shown promise for use with young children with autism spectrum disorder to increase a variety of social-communication behaviors. This study examined the manner in which parents acquired and used a set of responsive parenting techniques with their young children with fidelity and investigated the associations of fidelity use of these techniques with changes in child joint engagement outcomes. Although parents began the training phase demonstrating low levels of responsive parenting behaviors, they acquired and implemented a specific set of responsive parent techniques with their children with ongoing fidelity, and the use of these techniques was collaterally associated with increased levels of joint engagement in two of the three participant children. Implications for research and practice are discussed.